IMPACT OF SOCIAL MEDIA ON CONSUMER BEHAVIOR: ANALYSIS OF TRENDS AND CHALLENGES - Bilyk , I.I.; Kolisnyk , V.S. (The actual problems of regional economy development, 2023)
The article examines important aspects of social media use in the modern world. Based on statistics on the number of consumers on social networks around the world, the article highlights the main reasons that motivate users to use social media. Although Generation Z and millennials say that the main reason for their presence on such platforms is to spend their free time, statistics show otherwise - in fact, social media is mostly used to research products and services. The article also analyzes social media trends for 2023. In particular, it considers influencer marketing as one of the main trends that affects consumers through the use of influencers, or so-called influencers, in advertising campaigns. There are studies that show that their recommendations are one of the most important factors for consumers when deciding to purchase a particular product. The role of artificial intelligence in the context of social media is also noted, as AI can analyze large amounts of consumer data, including their profile, demographics, interests, and online behavior, and improve the personalization of content and advertising based on this information. Another trend described in the article is the growing popularity of short video content. Thanks to the rapid development of technology and the growing access to the mobile Internet, short videos have become extremely popular among social media users. In addition to trends, the article points out five challenges that brands face when using social media. They include: identifying the most effective platforms for brand promotion, as different people use different social networks depending on their age and needs; creating engaging content, which can be time-consuming and resource-intensive; finding ideas for new content, as social platforms are already overflowing with various materials; measuring ROI, as the goals pursued by businesses in social media are rather abstract, making it difficult to assess the success of activities; creating content that is engaging and relevant to the audience; This article is a valuable source of information for marketers, business owners, and social media professionals who want to understand the impact of social media on consumer behavior, as well as to be aware of the trends and challenges in this area in 2023.